Splenic Hemangioma as a Potential Pitfall on PSMA-Targeted 18F-DCFPyL PET/CT. (March 2019) - Chaussé, Guillaume; Laufer, Jerome; Abikhzer, Gad; Probst, Stephan
Abstract : Abstract: A 69-year-old man with biochemical recurrence after radical prostatectomy underwent 6 months of androgen deprivation therapy. Upon discontinuation of androgen deprivation therapy, serum prostate-specific antigen rose again to 0.69 ng/mL, and 18 F-DCFPyL PET/CT was performed to identify the site of recurrence. However, only an intense focus of uptake in the spleen could be found. Subsequent contrast-enhanced MRI findings were pathognomonic for splenic hemangioma.